PENDIDIKAN SISWA BERKEBUTUHAN KHUSUS MELALUI PEMBELAJARAN STEM - Nuraini Nuraini (JIP: Jurnal Ilmu Pendidikan, 2025)
STEM learning for students with special needs indicates an approach to learning that formulates the content of teaching materials in an integrated manner between the fields of science, technology, engineering, and mathematics (STEM). This approach integrates these scientific fields in a constructive and contextual manner in the learning process. The teaching materials are taken and combined from these four scientific fields to form a unified whole that is integrated into the learning outcomes achieved by the students. The steps of STEM learning, direct activities, and the best STEM lessons involve practical activities where students can directly engage in learning, from designing concepts to making or building something themselves. This greatly reduces the likelihood of students becoming bored or distracted. Mimicking real-life scenarios is another reason why hands-on learning is so important. One of the most important things in STEM is helping students learn skills and get used to them so that they can be useful to them in their future work. Integrate mathematics and science into projects seamlessly. Mathematics and science tailored to students must be relevant to their current projects, connected to real-world scenarios, and ultimately have a purpose. For example, mathematical equations ensure that a design functions properly, or physics knowledge helps them understand how to build something.